The effect of farnesol on the cAMP-PKA signaling pathway of Candida albicans biofilms and its correlation with drug resistance - WANG Yang, CHEN Xueyi, YU Shenjun, CAO Xuejiao, WEI Xin, YANG Xuan (Kouqiang yixue)
Objective To explore the regulatory role of farnesol in Candida albicans (C. albicans) biofilm cAMP-PKA signaling pathway and its correlation with drug resistance. Methods Standard, fluconazole-resistant, wild and high RAS1 gene expression strains of C. albicans were cultured to different phases of the biofilm (6,12,24,36 h), and the sessile minimal inhibitory concentration 50%(SMIC50) of fluconazole were determined by XTT reduction after farnesol treatment. The regulatory effects of farnesol on the expression of genes related to the cAMP-PKA signaling pathway in standard and fluconazole-resistant strains of C. albicans, such as RAS1, CYR1, PDE2 were examined using qPCR; the effects of farnesol on the protein expression of the pathway were analyzed by Western blot. RAS1 gene expression of the wild and high RAS1 gene expression strains was measured by qPCR. Results ① Compared with the standard strain, resistant strains of C. albicans had higher levels of biofilm SMIC50 at 6, 12 and 24 h; there was no significant difference in RAS1 expression (P>0.05), while CYR1 expression increased significantly at 6 and 24 h in the biofilm (P<0.01), and PDE2 expression decreased at 6 h in the biofilm (P<0.01). ②After treatment with farnesol, the resistance of the biofilm of the standard strain and drug-resistant strain decreased. Compared with no treatment with farnesol, the expression of RAS1 in the biofilm of the standard strain and drug-resistant strain decreased at all time points (P<0.01); CYR1 expression decreased in the biofilm at 6, 24 and 36 h, and increased in the biofilm at 12 h (P<0.01); PDE2 expression increased in the 12 h biofilm (P<0.01). ③Compared with the wild strain, the high expression strain of RAS1 gene showed higher SMIC50 in the biofilm at 12 and 24 h, and significantly higher expression of RAS1 gene in the biofilm at 12, 24 and 36 h (P<0.01). ④After treatment with farnesol, the resistance of wild-type strains and high expression strains of RAS1 gene decreased. Compared with the untreated group, the expression of RAS1 gene in the biofilm of wild-type and RAS1 gene high expression strain decreased at 12 and 24 h (P<0.01). Conclusion Farnesol can affect the sensitivity of C. albicans biofilm to fluconazole by regulating the expression of resistance molecules RAS1, CYR1 and PDE2 in the cAMP-PKA pathway. The regulatory effect varies at different stages of biofilm formation.